IMPACT OF COVID-19 PANDEMIC ON PROJECT PORTFOLIO MANAGEMENT-A CASE STUDY ON CONSTRUCTION INDUSTRY IN SOUTHERN INDIA - Krishnan, Ajay; S, Ajithkumar; G, Manishankar; K, Upendra; A, Kabilan; Muralidhar, P (Journal of Civil Engineering, Science and Technology, 2021)
In India, Project Portfolio Management (PPM) is in practice as a tool for prioritizing and managing real estate projects in construction organizations. But due to insufficient funding, improper judgment of experts during the crisis situation, the selection of optimal project portfolio prototype can be viewed as a risk based decision making process involving various risk factors. The objective of this study is to analyze the importance of project portfolio management and the risks associated with it in the construction industry taking into account the impact of novel corona virus COVID-19. This research identifies the adoption of more consistent project governance, risk management techniques and way more careful project portfolio management as the core area of study. A conceptual framework for Project Portfolio Management is also designed after analyzing various parameters of Project Portfolio Management of construction industry with the help of Bayesian framework. The key motive for undertaking this part of examination on real estate sector of Indian construction industry in southern part of India to reduce the impacts and increase the return on investment from the projects by mitigating the effect of risk factors associated in the projects. Project Portfolio Management tools and techniques are very useful for managing multiple construction projects.